Parietin as an efficient and promising anti-angiogenic and apoptotic small-molecule from Xanthoria parietina - Varol,Mehmet (2019)
ABSTRACT Lichens that are exclusive symbiotic organisms composed of fungus and alga, are considered as a wealthy source of biologically and pharmacologically active small-molecules thanks to the tight metabolic relationship between symbiotic partners. We herein report cytotoxic, anti-angiogenic and apoptotic profile of a lichen derived small-molecule named parietin. Parietin was isolated from the acetone extract of Xanthoria parietina (L.) Th.Fr (1860), Teloschistaceae, which was gathered from Afyon, Turkey. AlamarBlue™ cell viability, lactate dehydrogenase membrane leakage and PicoGreen™ dsDNA quantitation assays were used to determine the cytotoxic concentrations of parietin on cisplatin-resistant BRCA2-mutated human breast TNM stage IV adenocarcinoma (HCC1428), human breast ductal carcinoma (T-47D), and human umbilical vein endothelial (HUVEC) cells. Additionally, cell adhesion, endothelial tube formation, reactive oxygen species accumulation and active caspase 3 determination assays were employed to identify the anti-angiogenic and apoptotic efficiency of parietin. Low concentrations of parietin such as 50 and 100 µM showed a significant anti-angiogenic and apoptotic activity though the half-maximal inhibitory concentration (IC50) values were higher than 600 µM on the cells. On the other hand, it was observed that parietin shows less cytotoxic and membrane degradative activities on healthy HUVEC cells than the HCC1428 and T-47D breast cancer cells. Parietin seems to be a promising anti-angiogenic and apoptotic lichen metabolite for the further investigations.